Isolation and characterisation of antiplasmodial compounds from Xerophyta species and the bioavailability, metabolic and efficacy evaluation of 9-0-acetylhydnocarpin in a mouse model - Wiesner, Lubbe (Division of Clinical Pharmacology, 2014)
Includes abstract. Includes bibliographical references (leaves 237-265).